Primary pancreatic hydatid cyst: an unexpected differential diagnosis - Hiremath, Bharati (BMJ Case Rep, 2015)
Hydatid disease, caused by the cystic stage of Echinococcus granulosus, most commonly involves the liver (59–75%) and lung (27%), and rarely involves the kidney (3%), bone (1–4%) and brain (1–2%). Even rarer sites include the heart and spleen, and skeletal muscle, with virtually no site being immune. The pancreas is an exceedingly rare site for primary disease (without concomitant involvement of the liver or peritoneum), with less than 20 reported cases in the literature. This case report describes a 48-year-old woman presenting with a solitary cystic lesion arising from the neck of the pancreas, which was ultimately determined to be a hydatid cyst on histopathological examination. It also discusses the difficulties in preoperative and postoperative management and includes a review of the literature.